Conformation-sensitive targeting of CD18 depletes M2-like tumor-associated macrophages resulting in inhibition of solid tumor progression - Deok-Sang Hwang; Hyunsu Bae; Yingying Cao; Se Eun Lim; Ik-Hwan Han; Ilseob Choi; Hongseo Choi; Soyoung Kim; Chanmi Jeong; Juwon Yang; Jeongyoon Choi; Heekyung Lee; et al. (Journal for ImmunoTherapy of Cancer)
Background Tumor-associated macrophages (TAMs) primarily exist in the M2-like phenotype in the tumor microenvironment (TME). M2-TAMs contribute to tumor progression by establishing an immunosuppressive environment. However, TAM targeting is hindered, mainly owing to a lack of specific biomarkers for M2-TAMs. Previously, we demonstrated that a novel peptide drug conjugate (TB511) consisting of a TAM-binding peptide and the apoptosis-promoting peptide targets M2-TAMs. This was achieved through M2-TAM targeting, although the target mechanism of action remained elusive. Herein, we elucidate the anticancer efficacy of TB511 by identifying new target proteins that preferentially bind to M2-TAMs and clarifying the apoptosis-inducing mechanism in these cells.Methods We investigated the target proteins and binding site of TB511 using LC-MS/MS analyses, surface plasmon resonance and peptide–protein interaction 3D modeling. Activated CD18 expression in M2 TAMs was assessed using Quantibrite PE beads in PBMCs. The anticancer efficacy of TB511 was tested using colorectal cancer (CRC) and non-small cell lung cancer (NSCLC) mouse model. The immunotherapeutic effect of TB511 was investigated through spatial transcriptomics in human pancreatic ductal adenocarcinoma (PDAC) model.Results Activated CD18 was highly expressed in human tumor tissues and was significantly higher in M2 TAMs than in other immune cells. TB511 showed high binding affinity to CD18 among the cell membrane proteins of M2 macrophages and appeared to bind to the cysteine-rich domain in the activated form. Moreover, TB511 specifically induced apoptosis in M2 TAMs, but its targeting ability to M2 macrophages was inhibited in CD18 blockade or knockout model. In mouse or humanized mouse models of solid tumors such as CRC, NSCLC, and PDAC, TB511 suppressed tumor growth by targeting M2-TAMs via CD18 and enhancing the presence of CD8+ T cells in the TME.Conclusions Collectively, our findings suggest that activated CD18 holds promise as a novel target protein for cancer therapy, and TB511 shows potential as a therapeutic agent for tumor treatment.